Quality control of cellular protein in neurodegenerative disorders - Sahab Uddin, Md., 1992-; Ashraf, Ghulam Md, 1984- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2020)
"This book examines the diverse aspects of protein quality control systems and potential therapeutic approaches to halt the development and propagation of neurodegenerative disorders"--Provided by publisher.